2022
DOI: 10.1155/2022/4158692
|View full text |Cite|
|
Sign up to set email alerts
|

Rosiglitazone Alleviates Contrast-Induced Acute Kidney Injury in Rats via the PPARγ/NLRP3 Signaling Pathway

Abstract: Background. This study investigated the effect and mechanism of rosiglitazone on a rat model with contrast-induced acute kidney injury (CI-AKI). Materials and Methods. The CI-AKI rat model was established from Sprague Dawley rats by furosemide injection (10 ml/kg) to the caudal vein followed by iohexol (11.7 ml/kg). The experimental grouping was randomly allocated into control, model, rosiglitazone, and T0070907 groups. Blood samples were collected from the abdominal aorta. Serum creatinine, urea nitrogen, MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has also been reported that apoptosis influences the pathological changes associated with kidney injury [24]. In the present study, we used a TUNEL staining assay and Western blotting assay to comprehend the effects of treatment with SOP on ISO-induced renal apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been reported that apoptosis influences the pathological changes associated with kidney injury [24]. In the present study, we used a TUNEL staining assay and Western blotting assay to comprehend the effects of treatment with SOP on ISO-induced renal apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%